Relações mutualísticas e antagônicas entre insetos e (L.) Rich (Malpighiaceae) em área de Cerrado - Souza, Livia Aparecida de (2015)
The Brazilian Savannah hosts a wide diversity of species that shows wide range of plant-animal interactions which take importance in the formation and structure of this biome. Among the main plant families present, there is the Malpighiaceae, known for the diversity of species and especially for fruit production, widely used in feed for various animal species, particularly insects. Byrsonima verbascifolia (L.) Rich, popularly known as murici, displays multitrophic interactions involving plants, ants and other floral visitors. Although it is a vegetable of great ecological and economic importance, few are the information about its phenology and, specially, about the interactions that maintains with other organisms. This research had as objectives to describe this specie’s phenology during one biological cycle, evaluate the floral visitation rate in the presence and absence of ants and relate the floral visiting insects and frugivores. The experiments were performed in strict sensu Brazilian Savannah area, in a Biological Reserve in southern of Minas Gerais State. In the phenology study, the plants were monitored fortnightly during twelve months aiming the quantification of leafs, flower buds, inflorescences, infructescenses, and plants’ height. It was observed visitor specimens in flower buds and inflorescences for the ants’ effect evaluation in the floral visitation, with and without exclusion of ants. It was observed that the plants presented continuous growth along production period of leafs, flower buds, inflorescences and infructescenses. There was a higher number of floral visitors in plants where the ants were excluded. The most frequent floral visitors were represented by Hymenoptera species, mainly stingless bees (Trigona sp.), which were frequently observed rasping the floral oil-producing glands. In direct association with the fruits were found immature of the orders Lepidoptera, Coleoptera and Diptera. Parasitoid Hymenoptera and representatives of Blattodea, Hemiptera and Thysanoptera were also observed inside of the cages. With this research it is possible to know the phenology of B. verbascifolia, demonstrate the ants’ influence over the floral visitation rate and know several Insecta groups associated to the reproductive phase of this Malpighiaceae.